Chloride penetration into carbonated concrete - Malheiro, Raphaele Lira Meireles Castro (2016)
To ensure the durability of concrete structures it is necessary to understand its behaviour in the presence of aggressive agents. Carbonation and chloride action are the two leading causes of degradation in reinforced concrete structures. Â Despite the combined action of these two mechanisms being a reality, there is little research on the effect of CO2 presence on the chloride behaviour in concrete. This work studies the total chlorides ingress into carbonated concrete. For this, samples with CEM I 42.5R were cast with 0.6 of water/binder ratio. After 90 days of the curing period, half of the samples were subjected to accelerated carbonation (20ÂºC, 55%Relative Humidity and 4%CO2) for 1 month. The other half was protected with a plastic film during the same period. Chloride immersion test, based on LNEC E390 (Portuguese specification), were performed with samples subjected to both experimental conditions. Afterwards, the depth of chlorides and CO2 penetration was evaluated. The results show that, for these conditions, the CO2 presence has a direct influence on chloride behaviour. The non-carbonated samples showed a profile with a higher amount of chloride than carbonated ones.